Building a Quality Practice in Chronic Pancreatitis. Issue 3 (3rd March 2023) - Kothari, Darshan; Ketwaroo, Gyanprakash; Sheth, Sheth G.
Abstract : Chronic pancreatitis (CP) is a fibroinflammatory disorder that results in irreversible scarring to pancreatic parenchyma and presents with a myriad of symptoms including abdominal pain, nausea, weight loss, steatorrhea, and diabetes. Furthermore, patients with CP often have comorbid chemical dependencies to alcohol and tobacco, which can further complicate the management of CP. Recent literature proposes guidelines on how best to care for patients with CP and establishes requirements for centers of excellence. Here, we review the available data on endoscopic therapies, pain management, chemical dependency, and nutrition for patients with CP and propose quality metrics that may be used to establish a quality practice.